Agent-as-a-service-based geospatial service aggregation in the cloud: A case study of flood response. (October 2016) - Tan, Xicheng; Di, Liping; Deng, Meixia; Huang, Fang; Ye, Xinyue; Sha, Zongyao; Sun, Ziheng; Gong, Weishu; Shao, Yuanzheng; Huang, Cheng
Abstract: An Agent-as-a-Service (AaaS)-based geospatial service aggregation is proposed to build a more efficient, robust and intelligent geospatial service system in the Cloud for flood emergency response. It involves an AaaS infrastructure, encompassing the mechanisms and algorithms for geospatial Web Processing Service (WPS) generation, geoprocessing and aggregation. The method has the following advantages: 1) it allows separately hosted services and data to work together, avoiding transfers of large volumes of spatial data over the network; 2) it enriches geospatial service resources in the distributed environment by utilizing the agent cloning, migration and service regeneration capabilities of the AaaS, solving issues associated with lack of geospatial services to a certain extent; 3) it enables the migration of services to target nodes to finish a task, strengthening decentralization and enhancing the robustness of geospatial service aggregation; and 4) it helps domain experts and authorities solve interdisciplinary emergency issues using various Agent-generated geospatial services. Graphical abstract: Highlights: Agent-as-a-Service (AaaS)-based geospatial service aggregation on the Cloud is proposed. It allows separately-hosted services and data to work together, which avoids transferring large volume of spatial data. It enriches geospatial service resources in the distributed environment and solves the issue of lack of geospatial services. It strengthens decentralization and enhances robustness of the geospatial service aggregation. It provides experts assistance in solving the interdisciplinary emergency issues with agent-generated geospatial services.